Pseudosophronia exustellus (Zeller, 1847) a new species for the Maltese Islands (Lepidoptera: Gelechiidae) - A. Seguna; P. Sammut; A. Catania; J. J. Borg (SHILAP, 2022)
The genus Pseudosophronia Corley, 2001 and the species Pseudosophronia exustellus (Zeller, 1847) are recorded for the first time from the Maltese Islands. Notes on the distribution and habitat are included.